PERLINDUNGAN HUKUM BAGI PEMBELI ATAS TANAH REDISTRIBUSI YANG DIALIHKAN SECARA MELAWAN HUKUM (Analisis Putusan Pengadilan Nomor 170/PDT/2019/PT.DPS) - Ariyuda, I Made; Kusuma, Putu Riski Ananda; Dantes, Komang Febrinayanti (Jurnal Ilmu Hukum Sui Generis, 2025)
This research analyzes the complexity of the problem of unlawful redistribution land transfers and the protection efforts for aggrieved buyers. The main focus is to understand the extent to which the Indonesian positive legal framework protects third parties, especially buyers, in land sales and purchases that are declared invalid. In addition, this study analyzes the legal considerations in Denpasar High Court Decision Number 170/PDT/2019/PT.Dps related to the transfer of redistributed land. The purpose of this study is to provide concrete legal recommendations to strengthen the legal position of buyers in the transfer of rights to redistributed land that is not in accordance with the provisions. Using normative legal research methods with statutory, case, and conceptual approaches, data is collected through literature studies and regulatory documents and court decisions. The study found that the transfer of rights in the case under study was done without authorized consent, making it an illegal act. The judge declared the sale invalid and returned the land rights to the rightful heirs. However, the study also uncovered a normative void in the regulation that explicitly provides legal protection for unauthorized purchasers of redistributed land. This absence of regulation creates legal uncertainty and places buyers in a vulnerable position, often incurring financial losses without adequate remedy mechanisms. Through a normative legal approach, this study emphasizes the need for regulatory reform. Recommendations include strengthening preventive legal protections, such as increased transparency of land data, public education, active role of PPAT in verification, and special markings on redistribution certificates. In addition, repressive protection through civil suits for compensation and criminal sanctions for perpetrators of manipulation are also needed. This reform is essential to create legal certainty and ensure justice for all parties in land redistribution transactions in Indonesia.